Browning and Graying: Novel Transcriptional Regulators of Brown and Beige Fat Tissues and Aging - Mueller, Elisabetta (Frontiers in Endocrinology, 2016)
Obesity represents a major risk factor for the development of a number of metabolic disorders, including cardiovascular disease and type 2 diabetes. Since the discovery that brown and beige fat cells exist in adult humans and contribute to energy expenditure, increasing interest has been devoted to the understanding of the molecular switches turning on calorie utilization. It has been reported that the ability of thermogenic tissues to burn energy declines during aging, possibly contributing to the development of metabolic dysfunction late in life. This review will focus on the recently identified transcriptional modulators of brown and beige cells and will discuss the potential impact of some of these thermogenic factors on age-associated metabolic disorders.